2014
DOI: 10.1097/wco.0000000000000130
|View full text |Cite
|
Sign up to set email alerts
|

C9orf72 amyotrophic lateral sclerosis and frontotemporal dementia

Abstract: Purpose of reviewThe molecular mechanisms that underlie chromosome 9 open reading frame 72 (C9orf72)-associated amyotrophic lateral sclerosis and frontotemporal dementia are rapidly emerging. Two potential disease mechanisms have been postulated – gain or loss of function. We provide an overview of recent advances that support or oppose gain-of-function and loss-of-function mechanisms.Recent findingsSince the discovery that a noncoding repeat expansion in C9orf72 was responsible for chromosome 9-linked amyotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 64 publications
(149 reference statements)
0
57
0
4
Order By: Relevance
“…astrocytes and immortalized cell lines) were incubated with the synthetic peptides (Kwon et al, 2014). Toxicity of these arginine-rich peptides was also shown in vivo , in Drosophila models (Mizielinska and Isaacs, 2014). Another study showed, instead, that a different RAN translated species, poly-GA, caused toxicity measured by increased release of LDH, caspase-3 activation and endoplasmic reticulum stress when expressed in cultured cells and primary neurons (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…astrocytes and immortalized cell lines) were incubated with the synthetic peptides (Kwon et al, 2014). Toxicity of these arginine-rich peptides was also shown in vivo , in Drosophila models (Mizielinska and Isaacs, 2014). Another study showed, instead, that a different RAN translated species, poly-GA, caused toxicity measured by increased release of LDH, caspase-3 activation and endoplasmic reticulum stress when expressed in cultured cells and primary neurons (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…The pathogenic elements of C9ORF72 that involve both RNA and protein toxicity interact downstream with a large number of proteins, enzymes, and messengers, many of which have not yet been identified [79].…”
Section: Gene Therapy For C9orf72mentioning
confidence: 99%
“…The biological role of the proteins codified by the gene analyzed in the present study is complex; firstly, their functions in cellular processes seem to be related to the gene expression regulation, including RNA splicing and transport [11,21]. The expansion of C9orf72 gene induce the formation of repeat RNA aggregates that are shown to sequester proteins involved in RNA splicing, editing, nuclear export and nucleolar function [22]. The overexpression of TDP-43 is shown to induce the activation of a transcription factor nuclear, NF-κB that is the master regulator of inflammation via the expression of several genes.…”
Section: Discussionmentioning
confidence: 98%
“…Its function in cellular processes involves the regulation of membrane trafficking and gene expression [21]. The expansion of C9orf72 gene induces the formation of repeat RNA aggregates that are shown to sequester proteins involved in RNA splicing, editing, nuclear export and nucleolar function [22]. The mechanism by which the expanded GGGGCC repeat could induce neurodegeneration is considered to be mediated by three mechanisms independent but not mutually exclusive: the mt C9orf72 toxicity haploinsufficiency, the generation of toxic RNA foci and peptide accumulation in neurons [23,24].…”
Section: Introductionmentioning
confidence: 99%